Tinjauan Pemikiran Abdurrahman Wahid Tentang Formalisasi Syari’at Islam - Abdul Aziz (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2018)
This paper wants to explore the obsession of formalization of Islamic law that must be formalized in the state system and the obligation to establish an Islamic state. This is important to remember, because until now there are still parties who want to include the Jakarta Charter into our Constitution. With the claim of establishing a state for the sake of Islam it is clearly contrary to democracy. Because the understanding is based on the rule of law on the one hand and the equal treatment of all citizens before the Law on the other side. Indonesia is a state of law, so the formalization of Islamic law must refer to state law. Therefore, the transformative paradigm for efforts to formalize Islamic law in the National legal system isn’t the right choice and provides greater prospects. Thus, formalizing Islamic law formally symbolically especially with the effort to establish an Islamic state of Indonesia, will only experience distortion and not give much good to Indonesian Muslims.